2018
DOI: 10.1186/s40813-018-0104-7
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of a ready-to-use combined Porcine circovirus type 2 and Mycoplasma hyopneumoniae vaccine in Denmark – a historical comparison of productivity parameters in 20 nursery and 23 finishing herds

Abstract: BackgroundIn practice, field evaluation of vaccine efficacy in individual herds is often based on a historical comparison of productivity data following initiation of vaccination. Being biased by time, this study design highly contrasts the more controlled, parallel-group design used for most initial vaccine efficacy studies but offers the possibility of including a larger number of animals and herds. As an important add-on to previous findings in controlled studies, the objective of this study was to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, our and these mentioned results contrasted with other studies where a significantly lower mortality was observed in vaccinated animals [48,53] compared to non-vaccinated ones. It is noteworthy that the present field studies were designed with vaccinated and non-vaccinated commingled within the same pens, so, globally, vaccinated pig benefits could be worsened and nonvaccinated detriments could be ameliorated due to an overall increase of infectious pressure for vaccinated animals and a lower one for non-vaccinated ones [53].…”
Section: Discussioncontrasting
confidence: 99%
“…However, our and these mentioned results contrasted with other studies where a significantly lower mortality was observed in vaccinated animals [48,53] compared to non-vaccinated ones. It is noteworthy that the present field studies were designed with vaccinated and non-vaccinated commingled within the same pens, so, globally, vaccinated pig benefits could be worsened and nonvaccinated detriments could be ameliorated due to an overall increase of infectious pressure for vaccinated animals and a lower one for non-vaccinated ones [53].…”
Section: Discussioncontrasting
confidence: 99%
“…This could be related to the fact that the V group and NV group animals were comingled in the same pen/room. In such a scenario (not frequent under field conditions), the infectious pressure of non-vaccinated piglets may have hindered the vaccine efficacy [47].…”
Section: Discussionmentioning
confidence: 99%